High Stakes in the Bazaar: Cryptocurrency Trading as a Game of Chance in Istanbul - Hassan, Wesam (Critical Gambling Studies, 2024)
This article examines cryptocurrency trading in Turkey, focusing on the ‘gamblification’ of this emerging market. Based on 18 months of ethnographic research (2021-2022) conducted during an economic crisis exacerbated by the COVID-19 pandemic, the research reveals how Turks engaged with cryptocurrencies are considering the structural parallels between trading and gambling. The article also incorporates the perspective of Turkey's Directorate for Religious Affairs (Diyanet), which has declared cryptocurrency trading impermissible, highlighting the tension between contemporary financial practices and traditional Islamic frameworks. The article links the perception of cryptocurrency trading as a modern game of chance, as articulated by research participants, to Turkey's economic instability and their technological shift from traditional state-regulated games of chance (lotteries, betting on sports, and horse racing) to cryptocurrency trading. My ethnographic method brings new empirical data and qualitative analysis to understand the cultural and religious dynamics shaping this emergent financial phenomenon in the under-studied context of Turkey. I argue that cryptocurrency adoption in Turkey is driven by more than economic necessity; it reflects a cultural transformation valuing modernity and innovation. Many Turks view cryptocurrency as a viable alternative to traditional financial systems and a representation of the future of money. This shift signifies a departure from conventional monetary practices and reflects a collective idealisation of the future of finance. The article thus illuminates how Turkish individuals navigate risk and speculation during economic crises, demonstrating their adaptability in engaging with non-monetary financial markets.